Interaction of Straw Mulching and Nitrogen Fertilization on Ammonia Volatilization from Oilseed Rape–Maize Rotation System in Sloping Farmland in Southwestern China - Li Yao; Hong Wang; Haitao Liu; Xie Wang; Yueying Wu; Lin Wang; Honglin Chen; Chaowen Lin (Plants)
Ammonia (NH3) volatilization caused by urea application has negative implications for human health, environmental quality, and the value of nitrogen fertilizers. It remains to be investigated how management strategies should be adopted to not only reduce NH3 volatilization but also improve nitrogen use efficiency (NUE) in the agriculture industry at present. Hence, a two-year field trial, including subplots, was conducted to simultaneously evaluate the effects of mulching treatments (NM: non-mulching; SM: straw mulching) and different fertilizer treatments (U: urea; U + NBPT: urea plus 1% N-(n-butyl) thiophosphoric triamide; U + CRU: the mixture of urea and controlled-release urea at a 3:7 ratio; U + OF: urea plus commercial organic fertilizer at a 3:7 ratio) on NH3 volatilization, crop production, and NUE in an oilseed rape–maize rotation system in the sloping farmland of purple soil in southwestern China between 2021 and 2023. Compared with NM + U, NH3 volatilization losses under the NM + U + NBPT, NM + U + CRU, and NM + U + OF treatments decreased, on average, by 64.13%, 17.39%, and 15.09% during the oilseed rape growing season but by 64.01%, 11.67%, and 10.13% during the maize growing season, respectively. An average increase in NH3 volatilization of 35.65% for the straw-mulching treatment was recorded during the oilseed rape season, while during the maize season, this parameter showed an increase of 10.69%, in comparison to NM + U. With the combination of urea with NBPT, CRU, and organic fertilizer, contrastingly, a reduction in NH3 volatilization was achieved under the SM + U + NBPT, SM + U + CRU, and SM + U + OF treatments. When compared with NM + U, the difference in the NUE between the NM + U + NBPT, NM + U + CRU, and NM + U + OF treatments was not significant in the oilseed rape season. The NUE was around 4.27% higher under NM + U + NBPT during the maize season (p < 0.05). Compared with NM + U, under the NM + U + NBPT, NM + U + CRU, and NM + U + OF treatments, consistently lower values of yield-scaled NH3 volatilization were noted: 13.15–65.66% in the oilseed rape season and 10.34–67.27% in the maize season. Furthermore, SM + U, SM + U + NBPT, SM + U + CRU, and SM + U + OF showed average annual emission factors (AEFs) of 14.01%, 5.81%, 12.14%, and 11.64%, respectively. Overall, straw mulching, along with the application of the mixture of NBPT and urea, was found to be the optimal strategy to effectively reduce the NH3 emissions in the purple soil areas of southern China.